Improved Rice Production Technologies in Uttarakhand Hills : - Singh, S.R.K.; Gautam, U.S.; Shukla, S.K.; Singh, D.K.; Pandey, S.K. (Indian Journal of Extension Education, 2010)
Rice is one of the important kharif crops of the Uttarakhand. There exists a substantial yield gaps (35-55 %) between yield at research farm and farmers’ fields. This study was conducted during kharif 2006 to find out the reasons for such gaps. Eleven recommended rice production technologies were tested in six villages for studying the extent of adoption and reversion. Results showed that farmers were inquisitive for high grain and straw yield, lodging resistant, good threshing ability, early to medium duration in a new rice variety. The main reasons for reversion were lack of timely and adequate availability of seeds of desired variety. Majority of the farmers (55.6 %) were medium level adopters. Among technologies, full scale adoption of organic manure was highest (86.7%) followed by line sowing (80.0%), seed rate (63.3%) and fertilizer application (53.3%). Major constraints in adoption were non-availability of quality seeds, lack of motivation for new technology, frequent subsidy in form of inputs, and lack of proper marketing facilities. Suitable strategies need to be worked out to make farmers high adopters of the technologies. Besides, factors responsible for reversion and constraints need to be addressed for sustaining adoption of rice production technologies. This will help in enhancing the rice production in the region, which would, in turn, impart livelihood security and reduce migration of the farmers from hills.